INFANT FEEDING PRACTICES IN THE RURAL AND URBAN AREAS IN DISTRICT ABBOTTABAD - Aziz, Farida; Khan, Jahangir A.; Ara, Roshan (Journal of Ayub Medical College Abbottabad, 1990)
This article summarises the findings of a field study of infant feeding patterns in Urban and Rural areas of District Abbottabad. The main purpose of this study was to find out the reasons of declining trend of breast feeding. Over 70% rural mothers had no education and about 93% did not go to school. Average duration of breast feeding was observed to be 5.8 months and 19.2 months in the urban and rural areas respectively. The degree of suckling in urban and rural women was 9.7% and 24.7% respectively. It was observed that in urban areas 96% infants received breast milk for first 4 months of their life and by 2 years this level was dropped to 31%. In rural areas mothers breast fed their babies for 2 years on the average. 57% rural mothers believed that breast feeding is natural thing to do. The most obvious reason for stopping breast feeding was the next pregnancy. Urban mothers preferred brand name cereals as compared to homemade, which are most commonly used by rural mothers.